Mutagenic scan of the H-N-H motif of colicin E9: implications for the mechanistic enzymology of colicins, homing enzymes and apoptotic endonucleases - Walker, David C. (Oxford University Press, 2002)
Colicin E9 is a microbial toxin that kills bacteria through random degradation of chromosomal DNA. Within the active site of the cytotoxic endonuclease domain of colicin E9 (the E9 DNase) is a 32 amino acid motif found in the H-N-H group of homing endonucleases. Crystal structures of the E9 DNase have implicated several conserved residues of the H-N-H motif in the mechanism of DNA hydrolysis. We have used mutagenesis to test the involvement of these key residues in colicin toxicity, metal ion binding and catalysis. Our data show, for the first time, that the H-N-H motif is the site of DNA binding and that Mg(2+)-dependent cleavage of double-stranded DNA is responsible for bacterial cell death. We demonstrate that more active site residues are required for catalysis in the presence of Mg(2+) ions than transition metals, consistent with the recent hypothesis that the E9 DNase hydrolyses DNA by two distinct, cation-dependent catalytic mechanisms. The roles of individual amino acids within the H-N-H motif are discussed in the context of the available structural information on this and related DNases and we address the possible mechanistic similarities between caspase-activated DNases, responsible for the degradation of chromatin in eukaryotic apoptosis, and H-N-H DNases.